Investor Logins and the Disposition Effect - Quispe-Torreblanca, Edika; Gathergood, John; Loewenstein, George; Stewart, Neil (Management Science, 2024)
Using data from an online brokerage, we examine the role of investor logins in trading behavior. We find that a new reference point is created when an investor logs in and views the investor’s portfolio. We observe this as a disposition effect on returns since last login in addition to the traditional disposition effect on returns since purchase. Further, these reference points produce a strong interaction such that even a small loss since last login nullifies the positive effect of a gain since purchase. This interaction follows if investors select the higher, more aspirational price as a reference point. This paper was accepted by Yuval Rottenstreich, behavioral economics and decision analysis. Funding: This work was supported by the Economic and Social Research Council [Grants ES/K002201/1, ES/N018192/1, ES/P008976/1, and ES/V004867/1] and the Leverhulme Trust [Grant RP2012-V-022]. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2022.00359 .